Nonlinear dynamic analysis and defect detection of gears - Er-raoudi, M.; Diany, M.; Aissaoui, H.; Mabrouki, M. (Journal of Mechanical Engineering Automation and Control Systems, 2022)
In the current work, the nonlinear dynamic behavior of an eight degrees of freedom gear system is investigated. Tooth crack is introduced into the model. The main sources of excitation are the time varying mesh stiffness (TVMS), time varying mesh damping, backlash and friction inter teeth. By using the potential energy method applied into the cantilevered beam, the TVMS is calculated. The backlash is considered as a dead zone. The effect of backlash, friction and tooth crack on the vibration frequencies is highlighted. The crack detection is based on the time-frequency analysis.